Goma da linhaça (Linum usitatissimum L.) para uso como hidrocolóide na indústria alimentícia - Monego, Magda Aita (2009)
This work aimed to assess the yield of extractions of the flaxseed gum (whole and ground) and meal flaxseed in different concentrations, and check the effect of adding flaxseed gum in beef burguer with different levels of fat in chemical composition, cooking, sensory and shelf life (storage for 90 days, a - 200C). In the concentration C7,5% was noted more yield for flaxseed gum extractions (whole and ground) and meal flaxseed (7,2; 18; 9%, respectively). Produced 85% of total fibre extract from flaxseed (whole), the meal flaxseed gum presented low this component (56%) and high protein content (36%). Both gums have great ability to Water Binding Capacity (approximately 17 per gram gum) and has not been verified syneresis in the concentrations in gel 1; 5; 2 and 2.5%. The meal flaxseed gum showed double capacity of fat retention in relation to the flaxseed gum. The flaxseed gum obtained more viscosity than the meal flaxseed gum in concentration 2g/L, but it was stable in pH between 4 - 6; meal flaxseed gum was broadly stable in band of pH (2 - 10). The flaxseed gum was employed in beef burger formulations, as a substitute of fat in the concentrations: 0; 0, 1; 0,3; 0,6 and 1%. Both in raw beef burguers or cooked, it was noted that the greater concentration flaxseed gum in the treatments, greater was the moisture and less fat content. There was no significant difference (p < 0,05) for the amounts of ash and protein in raw and cooked beef burguers. All the tests presented more yield and moisture retention when compared to the control (GL0%), only GL1% had significantly difference (p < 0,05). GL0,6% presented greater retention fat in relation to the other. Diminution in diameter was observed in the sample GL0,1%, followed by GL0,3%; GL0,6% and GL0% in ascending order. The GL0% and GL0,1% have greater machining force (p < 0,05) than GL0,3%, and GL0,6%. In sensorial analysis, the GL0,1% and GL0,3% obtained majors notes for attribute appearance, GL0% and GL0,1% to odour and taste attributes. For attributes color and texture, only the GL1% was rejected, the smaller notes. In the test of purchase attitude, GL0,1% received major notes, followed by GL0,3%; GL0%; GL0,6% and GL1%, in descending order of preference. The pH increased during the period of storage, ranging from 5,6 (day 0) 6,1 (day 90), but was within pH for meat suitable for consumption. All the tests have less value of TBARS than the control (GL0%) at the end of storage. Therefore, it is concluded that is possible to get beef burguer reduced in fat, with similar quality or better than conventional product with added flaxseed gum, representing a viable alternative replacement partial fat in this product